2013
DOI: 10.1016/j.neuint.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba prevents transient global ischemia-induced delayed hippocampal neuronal death through antioxidant and anti-inflammatory mechanism

Abstract: We have previously reported neuroprotective properties of Ginkgo biloba/EGb 761® (EGb 761) in transient and permanent mouse models of brain ischemia. In a quest to extend our studies on EGB 761 and its constituents further, we used a model of transient global ischemia induced delayed hippocampal neuronal death and inflammation. Mice pretreated with different test drugs for 7 days were subjected to eight-minute bilateral common carotid artery occlusion (tBCCAO) at day 8. After 7 days of reperfusion, mice brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…Neuroinflammation can cause neuronal death, but also confers neuroprotection by triggering antioxidant defenses system in the damaged neurons (Stoll et al 2002). Nrf2 antioxidant signaling pathway is one of the most important activated antioxidant pathways during cerebral ischemia/reperfusion in the experimental and clinical trial studies (Tulsulkar and Shah 2012;Guo et al 2013). Besides, it was reported that antioxidant related enzymes such as superoxide dismutase; catalase and glutathione which are Nrf-2/β-actin (Arbitrary unit)…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation can cause neuronal death, but also confers neuroprotection by triggering antioxidant defenses system in the damaged neurons (Stoll et al 2002). Nrf2 antioxidant signaling pathway is one of the most important activated antioxidant pathways during cerebral ischemia/reperfusion in the experimental and clinical trial studies (Tulsulkar and Shah 2012;Guo et al 2013). Besides, it was reported that antioxidant related enzymes such as superoxide dismutase; catalase and glutathione which are Nrf-2/β-actin (Arbitrary unit)…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms responsible for cell loss during cerebral ischemia are not yet fully understood, much important work has been done on the subject in recent years (8,26). Histopathological studies performed with a cerebral ischemia model have determined pronounced contraction in neurons, irregularities in cell and nuclear margins, and perineural and pericapillary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated changes in the chemical structures of existing drugs used in treatment or the development of new drugs for that purpose, while there are also studies regarding various plant essences found in nature. One of the most important of these plants is Ginkgo biloba (GB) (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid glycosides confer antioxidant properties to ginkgo particularly at the mitochondrial level while the terpenoids act as antagonists of platelet-activating factor [45][46][47][48]. In comparison to other antioxidants such as vitamin C or vitamin E, the extracts of ginkgo can stabilize and protect mitochondrial function [49][50][51] thereby preventing oxidative damage to mitochondria [49].…”
Section: Ginkgo Bilobamentioning
confidence: 99%